Comparison of The Histology of Goblet Cells the Intestinal Mucosa Colon Induced by Cayenne Pepper at Doses of 45 mg, 90 mg, 135 mg, 180 mg - Sherly Usman (Asosiasi Dosen Muda Indonesia, 2026)
This study aimed to analyze the effect of cayenne pepper (Capsicum frutescens L.) juice on the histological structure of colonic mucosal crypts and the number of goblet cells in Wistar rats. Cayenne pepper contains capsaicin, flavonoids, and vitamin C, which exhibit both pro-inflammatory and anti-inflammatory properties. Goblet cells play an essential role in maintaining intestinal homeostasis by producing mucin that protects the mucosa from inflammation. This quasi-experimental study employed a post-test only control group design using 20 male Wistar rats divided into one control group and four treatment groups receiving cayenne pepper juice at doses of 45 mg, 90 mg, 135 mg, and 180 mg daily for seven days. On day seven, the rats were terminated, and colon tissues were processed for histological examination using hematoxylin-eosin staining. Observations were conducted under 40× magnification to measure crypt length and count goblet cells. Data were analyzed using the Shapiro–Wilk normality test followed by one-way ANOVA. The results showed significant differences among groups (p<0.05). The 90 mg group exhibited the shortest mean crypt length, while the 135 mg group had the lowest number of goblet cells, indicating greater mucosal damage. In contrast, the 180 mg group demonstrated the longest crypt length and highest goblet cell count, suggesting mucosal repair. These findings indicate that cayenne pepper induces dose-dependent effects on colonic mucosa, with higher doses potentially promoting mucosal regeneration.